Validation of an infectious bronchitis virus GVIII-specific RT-PCR assay and first detection of IB80-like strains (lineage GVIII-2) in Italy - Legnardi, Matteo; Poletto, Francesca; Franzo, Giovanni; Harper, Valeria; Bianco, Luca; Andolfatto, Cristina; Blanco, Angela; Biarnés, Mar; Ramon, Laura; Cecchinato, Mattia; Tucciarone, Claudia Maria (Frontiers in Veterinary Science, 2024)
Infectious bronchitis virus (IBV) is a pathogen causing respiratory, renal and reproductive clinical forms in chickens of all ages and productive categories. Its proneness to mutation and recombination gave rise to a plethora of variants differing in terms of pathogenicity, antigenicity, and distribution, with relevant implications for disease control, mainly pursued by routine vaccination, and diagnosis, requiring a steady update of molecular and serological methods. Among the most recent additions to the current phylogenetic classification, based on S1 gene sequencing, is the discovery of an eighth genotype (GVIII), further divided into lineages GVIII-1 and GVIII-2. GVIII-2, whose best-known representative is IB80, has been reported since 2015 in Europe, the Middle East and Asia. Most detections occurred in layers and breeders and were possibly associated to egg production drops. However, experimental reproduction of its pathogenicity could not be achieved. The significant genetic divergence of GVIII from other genogroups prevents its detection by many of the commonly applied biomolecular tests, hampering the understanding of its spread and impact. This study describes the validation of a GVIII-specific RT-PCR assay and its application to analyze samples collected from layer farms in Italy, where the presence of this genotype has never been investigated. The in-house assay proved highly reliable and allowed to establish the circulation of GVIII-2 in the country: between April and June 2024, 11 out of 84 flocks (13.1%) in 5 out of 24 farms (20.8%) tested positive. Phylogenetically, all Italian strains clustered together, whereas their identity with IB80 was 96.8–97.7%. Reproductive signs were reported in one farm and respiratory signs in another, whereas no clinical findings were recorded in the remaining positive cases. Although no definitive conclusions are possible on their prevalence and clinical relevance, the obtained results suggest that the presence of GVIII-2 strains in Italy is neither novel nor sporadic, highlighting the need to revise diagnostic approaches and shed light on the epidemiology of this novel lineage.